Correlation Between PD-L2 Expression and Clinical Outcome in Solid Cancer Patients: A Meta-Analysis - Yang, Huayu; Zhou, Xiaoxiang; Sun, Lejia; Mao, Yilei (Frontiers in Oncology, 2019)
Background: Immune checkpoint inhibitors targeting the programmed cell death 1 (PD-1)/programmed cell death ligand 1 (PD-L1) pathway are a paradigm-shifting cancer therapy. Programmed cell death ligand 2 (PD-L2) is another ligand of PD-1, but its prognostic significance in solid cancer patients after surgery remains controversial. In this study, we aimed to reveal the prognostic implication of PD-L2 in solid tumors through a meta-analysis. Methods: We searched PubMed, Embase and the Cochrane library for studies reporting the relationship between PD-L2 expression and prognosis or clinicopathological features in solid cancer patients after surgery from inception to January 2018, with language restricted to English. Pooled hazard ratios (HRs) and 95% confidence intervals (CIs) were determined to explore the prognostic value of PD-L2 expression. Odds ratios (ORs) were also calculated to investigate the relationship between PD-L2 expression and clinicopathological parameters. Results: Sixteen studies incorporating 3,533 patients were included in our meta-analysis. The pooled results revealed that PD-L2 overexpression was a weak negative predictor for overall survival (OS; HR=1.38, 95% CI=1.05–1.81, P=0.021), as well as a strong predictor for poor disease-free survival (DFS)/progression-free survival (PFS) (HR=1.44, 95% CI=1.15–1.81, P=0.001). In subgroup analyses, high PD-L2 expression revealed an unfavorable prognostic prediction for OS in hepatocellular carcinoma (HCC) (HR=1.60, 95% CI=1.12–2.29, P=0.011) and for DFS/PFS in HCC (HR=1.50, 95%CI=1.04–2.16, P=0.031) as well as clear cell renal cell carcinoma (HR=1.45, 95% CI=1.03–2.03, P=0.033). Moreover, PD-L2 expression implied a weak trend towards the presence of lymphatic metastasis (presence vs. absence, OR=1.61, 95% CI=0.98–2.65, P=0.061). Conclusion: High PD-L2 expression may promote tumor metastasis and predict unfavorable prognosis in solid cancer patients after surgery, especially in HCC, and highlights PD-L2 as a promising immunotherapeutic target in solid tumors.